Violence in Animal Cruelty Offenders - Hoffer, Tia (SpringerBriefs in Behavioral Criminology,, 2018)
This book presents results from a BAU study including 259 active, animal cruelty cases. In addition, there were a total of 495 animal victims including numerous species, but dogs (64%) were the predominant animal victim. The offenders were all male, ranging in age from 17-years old to 82 years old (mean age of 34 years) and 73.44% had arrests for various other crimes prior to and/or following the instant animal cruelty arrest. Sixty percent of the offenders had been arrested for interpersonal violence prior, concurrent and/or post the instant active animal cruelty incident. .